Changes in the Positions of Selected European Metropolises in International Rankings - Jankowska, Marta (Studia Oeconomica Posnaniensia, 2015)
Contemporary metropolises significantly determine the competitive advantage of national economies and constitute a driving force of their development. The potential of these places consists of a number of factors that cannot always be investigated by means of hard indicators. Therefore, it is helpful to analyze the global rankings of cities that represent metropolises in terms of more subjective criteria. The article analyzes the changes of position of eight selected European metropolises in three international city rankings in the years 2007-2011. On this basis the conclusions about the possible reasons for the pace of changes in the level of cities development were drawn. Particular attention was paid to the importance of the quality of life in the city for the attractiveness of the metropolis.